Rābiṭah al-Muthaqqafīn al-Muslimīn al-Indūnīsīyah: Khalfīyatuhā wa Tumūhātuhā - Badri Yatim (Studia Islamika, 1994)
The Islamization of the legislative and the cabinet in Indonesia after the general election in 1992 has indeed provided interesting news. This is because of the old myth that the Muslim ummah are always opposed to the goverment. What is the driving force behind the change?DOI: 10.15408/sdi.v1i1.870